Comparative utility of disability progression measures in PPMS: Analysis of the PROMiSe data set. Issue 4 (July 2017) - Koch, Marcus W.; Cutter, Gary R.; Giovannoni, Gavin; Uitdehaag, Bernard M.J.; Wolinsky, Jerry S.; Davis, Mat D.; Steinerman, Joshua R.; Knappertz, Volker
Abstract : Objective: To assess the comparative utility of disability progression measures in primary progressive MS (PPMS) using the PROMiSe trial data set. Methods: Data for patients randomized to placebo (n = 316) in the PROMiSe trial were included in this analysis. Disability was assessed using change in single (Expanded Disability Status Scale [EDSS], timed 25-foot walk [T25FW], and 9-hole peg test [9HPT]) and composite disability measures (EDSS/T25FW, EDSS/9HPT, and EDSS/T25FW/9HPT). Cumulative and cross-sectional unconfirmed disability progression (UDP) and confirmed disability progression (CDP; sustained for 3 months) rates were assessed at 12 and 24 months. Results: CDP rates defined by a ≥20% increase in T25FW were higher than those defined by EDSS score at 12 and 24 months. CDP rates defined by T25FW or EDSS score were higher than those defined by 9HPT score. The 3-part composite measure was associated with more CDP events (41.4% and 63.9% of patients at 12 and 24 months, respectively) than the 2-part measure (EDSS/T25FW [38.5% and 59.5%, respectively]) and any single measure. Cumulative UDP and CDP rates were higher than cross-sectional rates. Conclusions: The T25FW or composite measures of disability may be more sensitive to disability progression in patients with PPMS and should be considered as the primary endpoint for future studies of new therapies. CDP may be the preferred measure in classic randomized controlled trials in which cumulative disability progression rates are evaluated; UDP may be feasible for cross-sectional studies.